Cachexia is an Insidious Symptom of Pancreatic Ductal Adenocarcinoma Associated with Delayed Diagnosis and Advanced Stage of Disease - Piciucchi, Matteo; Valente, Roberto; Stigliano, Serena; Archibugi, Livia; Zerboni, Giulia; Signoretti, Marianna; Larghi, Alberto; Costamagna, Guido; Delle Fave, Gianfranco; Capurso, Gabriele (JOP. Journal of the Pancreas, 2013)
Context Pancreatic ductal adenocarcinoma (PDAC) is an aggressive neoplasm, frequently presenting with cachexia that seems to retard the diagnosis and leading to worse prognosis. Molecular mechanism of cachexia are increasing explained, but its clinical features and its impacts on prognosis are still unclear. Objective To evaluate prevalence and features of a cachexia as presenting symptom of PDAC, clinical factors associated to its occurrence and its associated survival in PDAC patients. Methods Database retrospective analysis of prospective enrolled PDAC (Jan 2006 to Jan 2012): symptoms, tumor’s features and outcome of patients with cachexia (defined as weight loss >5 kg in the year before diagnosis) compared to those without it. Results Two-hundred and 91 PDAC patients enrolled: 144 (49.4%) presented cachexia (C+). C+ patients had similar medical history (chronic pancreatitis, diabetes, insulin and statin usage) than C-, but they were more frequently male (61.0% C+ vs. 46.5% C-; P=0.04) and overweight subjects (mean BMI: 28.6 kg/m2 C+ vs. 25.9 kg/m2 C-; P=0.0001). The onset symptoms other than cachexia were similarly frequent in C- and C+ patients, but for unspecific abdominal pain which was more frequent in C+ (56.4 %) than C- (40.8%; P=0.004). Patients with cachexia had a longer diagnostic delay than C- (4.81 months vs. 2.23 P=0001). C+ and C- patients had similar site and size of primary tumor, as well as histological grading, but C+ had more frequently distant metastasis at diagnosis (44.4% C+ vs. 32.6% C-; P=0.04) and a shorter, although non significantly, overall survival (7 vs. 11 months; P=0.19) compared to C-. Conclusion In our cohort of incident PDAC, about half of patients presented with cachexia. Cachexia was frequently associated with abdominal pain and with a diagnostic delay, and with a metastatic stage at diagnosis. The results suggest that unexplained weight loss and recurrent abdominal pain are under-evaluated symptoms of PDAC, and their investigation might lead to an earlier diagnosis of this aggressive disease.